2009
DOI: 10.1093/rheumatology/kep089
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A protein stimulates CCL20 production in rheumatoid synoviocytes

Abstract: These findings suggest that SAA may be implicated in the recruitment of lymphocytes, including CCR6-expressing Th17 cells, in RA synovium by up-regulating CCL20 production in synoviocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…JNK pathway is known to be involved in chemokines expression such as MIP-1, MIP-1β, and MIP-3α [4547]. These chemokines are also known to be produced by activated astrocytes [48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…JNK pathway is known to be involved in chemokines expression such as MIP-1, MIP-1β, and MIP-3α [4547]. These chemokines are also known to be produced by activated astrocytes [48].…”
Section: Resultsmentioning
confidence: 99%
“…For example, treatment with a JNK inhibitor inhibits production of CCL-2 (MCP-1) and CCL-4 (MIP-1β) in IL-1β- or TNF-α-stimulated trimester decidual cells [47]. JNK pathway is also involved in CCL-20 production in keratinocytes and Rheumatoid arthritis synoviocytes after inflammatory stimuli [45,46]. Furthermore, MCP-1 is produced by astrocytes via JNK-mediated pathway after SNL and involved in NP and central sensitization (hyperactivity of dorsal horn neurons) [16].…”
Section: Discussionmentioning
confidence: 99%
“…For example, SAA3 induces expression of CCL20 (MIP-3␣) (45). CCL20 is a ligand for CCR6, which is expressed on IL-17A ϩ ␥␦ T cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of SAA with FPRL1 stimulates endothelial cell proliferation, migration and angiogenesis, as well as synovitis [66,67]. It has been reported that SAA in part acts via the induction of MIP3a/CCL20 chemokine production by RA synovial fibroblasts [68 ]. MIP-3a/CCL20, as well as its receptor, CCR6, have been implicated in RA-associated inflammation and angiogenesis [44,69].…”
Section: Other Angiogenic Mediatorsmentioning
confidence: 99%